In Search of Place (poem) - H. C. Palmer (Symphony in the Flint Hills, 2014)
A poem by H.C. Palmer about entering the Flint Hills and shedding technology inorder to enjoy the nature.
Keywords: poem; poet; searching; search; prairie; Whitewater Falls; dirt road; 4 wheeler; Flint Hills